Transcriptomic Analysis Reveals Adaptive Responses of an Enterobacteriaceae Strain LSJC7 to Arsenic Exposure - Zhang, Yingjiao; Chen, Songcan; Hao, Xiuli; Su, Jian-Qiang; Xue, Ximei; Yan, Yu; Zhu, Yong-Guan; Ye, Jun (Frontiers in Microbiology, 2016)
Arsenic (As) resistance determinant ars operon is present in many bacteria and has been demonstrated to enhance As(V) resistance of bacteria. However, whole molecular mechanism adaptations of bacteria in response to As(V) stress remain largely unknown. In this study, transcriptional profiles of Enterobacteriaceae strain LSJC7 responding to As(V) stress were analyzed using RNA-seq and qRT-PCR. As expected, genes involved in As(V) uptake were down-regulated, those involved in As(V) reduction and As(III) efflux were up-regulated, which avoided cellular As accumulation. Reactive oxygen species and nitric oxide (NO) were induced, which caused cellular damages including DNA, proteins, and Fe-S clusters damages in LSJC7. The expression of specific genes encoding transcriptional regulators, such as nsrR and soxRS were also induced. NsrR and SoxRS modulated many critical metabolic activities in As(V) stressed LSJC7 cells, including reactive species scavenging and repairing the damages of DNA, proteins, and Fe-S clusters. Therefore, besides As uptake, reduction, and efflux, oxidative stress defense and damage repair were the main cellular adaptive responses of LSJC7 to As(V) stress.